PENGARUH NORMA SUBJEKTIF DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK HOTEL DAN RESTORAN - Ni Made Intan Priliandani; Komang Adi Kurniawan Saputra (KRISNA: Kumpulan Riset Akuntansi, 2019)
The biggest contribution from state revenues is from tax. Taxes are used for development from the center to the development in each region. The central government has authorized local governments to determine their own local tax policies in collecting or managing local taxes. Efforts made by the government in increasing taxpayer compliance is to provide motivation to taxpayers to obey paying taxes, mengadaka tax socialization, supervise and implement strict tax sanctions. This study examines the Subjective Norm Effect, and Tax Socialization to see the effect on Hotel and Restaurant Taxpayer Compliance. The formulation of the problem in this research is whether subjective norms and taxation socialization have an effect on hotel and restaurant taxpayer compliance. This research aims to prove empirically the influence of subjective norms and tax socialization on hotel and restaurant taxpayer compliance. This research was held at the Regional Revenue Agency of the City of Denpasar with a population of 93 samples. The sampling method used proportionate stratified random sampling, so the sample in this study amounted to 36 hotels and 57 restaurant tax payers. The analytical method used was the method of multiple linear regression analysis. The results of this research indicate that subjective norms and tax socialization have a positive effect on hotel and restaurant taxpayer compliance. Keywords: Accounts Receivable Turnover; Economic Rentability; Rentability of Own Capital; Working Capital Turnover.